2019
DOI: 10.1111/cge.13557
|View full text |Cite
|
Sign up to set email alerts
|

16p13.11 microdeletion uncovers loss‐of‐function of a MYH11 missense variant in a patient with megacystis‐microcolon‐intestinal‐hypoperistalsis syndrome

Abstract: Megacystis‐microcolon‐intestinal hypoperistalsis syndrome (MMIHS), a rare condition that affects smooth muscle cells, is caused by biallelic null alleles in MYH11. We report on a girl with MMIHS in addition to growth hormone deficiency, central hypothyroidism and a tonically dilated pupil with accommodation deficit. Sanger sequencing and arrayCGH uncovered the novel heterozygous missense variant c.379C>T in MYH11 and a heterozygous 1.3 Mb deletion in 16q13.11 encompassing MYH11, respectively. Her mother car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…In addition to the association with TAAD/PDA, four individuals with MYH11 mutations have been reported with MMIHS, a recessive disease characterized by impaired intestinal motility likely caused by smooth muscle degeneration through a loss‐of‐function mechanism (MIM# 155310). MYH11 mutations from this cohort include one homozygous nonsense variant, two compound heterozygous frameshift variants, a compound heterozygous missense variant and 1.3 Mb deletion in 16p13.11 that includes MYH11 , and a compound heterozygous missense variant and indel (Gauthier et al, 2015; Kloth et al, 2019; Q. Wang et al, 2019; Yetman & Starr, 2018). Mutations in ACTG2, MYL9, LMOD1 , and MYLK , which encode other smooth muscle proteins, have also been implicated in MMIHS disease pathogenesis (Halim, Brosens, et al, 2017; Halim, Wilson, et al, 2017; Moreno et al, 2018; Thorson et al, 2014; Wangler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the association with TAAD/PDA, four individuals with MYH11 mutations have been reported with MMIHS, a recessive disease characterized by impaired intestinal motility likely caused by smooth muscle degeneration through a loss‐of‐function mechanism (MIM# 155310). MYH11 mutations from this cohort include one homozygous nonsense variant, two compound heterozygous frameshift variants, a compound heterozygous missense variant and 1.3 Mb deletion in 16p13.11 that includes MYH11 , and a compound heterozygous missense variant and indel (Gauthier et al, 2015; Kloth et al, 2019; Q. Wang et al, 2019; Yetman & Starr, 2018). Mutations in ACTG2, MYL9, LMOD1 , and MYLK , which encode other smooth muscle proteins, have also been implicated in MMIHS disease pathogenesis (Halim, Brosens, et al, 2017; Halim, Wilson, et al, 2017; Moreno et al, 2018; Thorson et al, 2014; Wangler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The variant locates at the end of the protein and elongates the protein. Although recessive genotypes in MYH11 were reported in three separated case (one homozygotes and two compound‐heterozygotes) as a cause of megacystis‐microcolon‐intestinal hypoperistalsis syndrome (Supplementary Figure 1), heterozygous MYH11 pathogenic variants have not been previously reported in CIPO. Heterozygous pathogenic MYH11 variants were reported for Thoracic Aortic Aneurysm and/or aortic Dissection (TAAD) and Patent Ductus Arteriosus .…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the contractile apparatus components and pathogenic variants in the protein impair its polymerization and result in the reduced cellular contractility . Additionally, homozygous mutations in MYLK , MYH11 , LMOD1 , MYL9 , and RAD21 and X‐linked mutation in FLNA have been found in a small number of cases. Moreover, compound‐heterozygous mutations in MYH11 have also been reported in two CIPO families .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genetic studies identified heterozygous pathogenic missense variations in the enteric smooth muscle Actin γ‐2 gene ( ACTG2 , MIM#102545), 4‐12 as the major genetic cause of MMIHS. Recently, homozygous or compound heterozygous variants have been identified, respectively in the smooth muscle myosin heavy chain gene ( MYH11 , MIM#160745), 13‐16 the Leiomodin1 gene ( LMOD1 , MIM#602715), 17 and in the myosin light chain kinase gene ( MYLK , MIM#600922) 18 . In addition, a homozygous deletion of exon 4 of MYL9 (MIM#609905) has been reported 19 .…”
Section: Introductionmentioning
confidence: 99%